Applications of ARIMA and GARCH models in Sarawak pepper volatility study - Bin Razali, Jelani (International Journal of Engineering and Technology, 2018)
This study analyses the Sarawak black pepper price at Kuching spot market volatility using both ARIMA and GARCH models to determine the best fit and accurate forecasting model for the price series. The findings indicates ARIMA (1,1,1) is a good model to forecast the price series but failed to fulfill the white noise assumption. GARCH (1,1) model is found to be the best fit model to model and forecast the price series. Evidence suggests that asymmetry effect is present in Sarawak black pepper price series with long memory volatility persistence.Â
Keywords: ARIMA; GARCH; Asymmetry; Price Forecast and Sarawak Pepper.